Development of a Mechatronic System for Rehabilitation of Injuries in the Radial Nerve - Avendaño-Santiago, J. P.; Arias-Montiel, M.; Guzmán-Ramírez, E. (Revista Mexicana de Ingenieria Biomedica, 2017)
This work presents the design, analysis and implementation of a mechatronic System focused on helping to improve Rehabilitation therapies to patients affected by some Radial Nerve Injuries (SYRR-NERI). The device was developed with the aim of finding simple solutions for the different subsystems that form the SYRR-NERI. The mechatronic system basically consists of two coupled four-bar mechanisms with a Proportional-Integral-Derivative (PID) controller in their respective drive motors to regulate the rotational velocity. In addition, each mechanism has touch sensors in order to limit its movement. The implementation of the control algorithm and the logic to perform the synchronized movements is performed by a microcontroller. The result is an affordable and functional prototype which needs to be tested in real situations with the help of physiotherapists and patients to obtain the necessary information to improve its performance.